The Effect of Additives on The Performance of Hydrostatic Thrust Bearings - Yousif, Albert E. (Al-Khwarizmi Engineering Journal, 2019)
The paper is concerned with, the behavior of the hydrostatic thrust bearings lubricated with liquid-solid lubricants using Einstein viscosity formula, and taking into account the centrifugal force resulting from high speed. Also studied is the effect of the bearing dimensions on the pressure, flow rate, load capacity, shear stress, power consumption and stiffness. The theoretical results show an increase in load capacity by (8.3%) in the presence of solid graphite particles with concentration of (16%) by weight as compared with pure oil, with increasing shear stress. . In general the performance of hydrostatic thrust bearings improve for load carrying capacity, volume flow rate, pumping power subjected to centrifugal parameter (S), recess position (r1), film thickness ratio (b), particle concentration (l).